Piranti Lunak Pengujian Struktur Matematika Grup, Ring, Field Berbasis Osp (Open Source Program) - Ngarap Im Manik; Don Tasman (ComTech: Computer, Mathematics and Engineering Applications, 2014)
This design of a computer software is a development and continuation of the software made on the previous research (2009/2010). However, this further research developed and expanded the scopes of testing more on the Siclic Group, Isomorphism Group, Semi Group, Sub Group and Abelian Group, Factor Ring, Sub Ring and Polynomial Ring; developed on the OSP (Open Source Program)-based. The software was developed using the OSP-based language programming, such Java, so it is open and free to use for its users. This research succeeded to develop an open source software of Java program that can be used for testing specific mathematical Groups, such Ciclic Group, Isomorphism Group, Semi Group, Sub Group and Abelian Group, and Rings, Commutative Ring, Division Ring, Ideal Sub Ring, Ring Homomorphism, Ring Epimorphism and Fields. By the results, the software developed was able to test as same as the results from manual testing.